A Comparison of the Current N2 Classification and a Modified N2 Categorization in TNM Staging of Esophageal Cancer Patients - Xi, Kexing; Yu, Hui (Frontiers in Oncology, 2021)
Objective: The purpose of this study was to evaluate N category of the 8th edition American Joint Committee on Cancer (AJCC) in esophageal cancer (EC) and proposal of a modified N2 category for TNM staging. Methods: 2283 esophageal cancer patients who underwent esophagectomy between 2004 and 2015 from the Surveillance, Epidemiology, and End Results (SEER) database were reviewed. A separate Chinese cohort (470 patients) were used to verify the results of SEER database. Result: A total of 2753 patients EC patients were enrolled in this study, including 2283 patients from SEER database and 470 patients from a Chinese single-institution database. Based on the number of metastatic LNs, the N2 category was divided into two groups according to the result of X-tile software. Patients with 3~4 metastatic LNs were defined as N2a and those with 5~6 metastatic LNs were defined as N2b. The 3-year overall survival (OS) rate in SEER database was 71.5%, 42.3%, 23.6%, 17.2%, 10.7% for patients with N0, N1, N2a, N2b, N3, respectively (P＜0.001). Furthermore, a separate Chinese cohort was enrolled to validate the revised N2 category. And the 3-year OS rate was 71.5%, 42.3%, 23.6%, 17.2%, 10.7% for patients with N0, N1, N2a, N2b, N3, respectively (P＜0.001). Conclusion: Current N2 category should be further classified into two groups (N2a and N2b). The revised N2 category may provide more accurate prognosis information, which might help to make personalized therapeutic strategies.